Three essays on cash holdings and corporate governance - Manoel, Aviner Augusto Silva (2020)
This thesis consists of three articles. In the first article, we analyze if the initiative of a domestic stock exchange that designed three high-governance listings of voluntary adoption, in addition to maintaining its traditional listing, can mitigate managers\' ability to expropriate cash holdings. As a consequence of the reduction in cash improper diversion in firms with stronger governance mechanisms, we hypothesize that shareholders place a higher value to cash in firms that voluntarily commit to the premium listing. Reforms of corporate law designed to protect minority shareholders face serious political opposition in Brazil. The creation of the special listing (Level I, Level II and New Market), as a private contractual arrangement, offers a unique setting to analyze if these mechanisms can mitigate managers ability to expropriate cash holdings at the expense of principal. The market value of cash is ultimately determined by how investors expect cash to be used. Consistent with our hypothesis, we find that shareholders assigns a higher value to cash in firms from the premium listing of corporate governance relative to corporations from the non-premium listing, ceteris paribus. In sum, these findings are consistent with agency theory and suggest that when expected agency problems are larger, shareholders identify the potential private benefits attached to cash and, thereby, discount their value. Furthermore, the analyzes show that investors place a higher value to cash in firms from the segment of the premium listing (New Market) with the highest standards, where companies follow the \"one share, one vote\" principle. This result suggest that the market anticipate that liquid assets are more likely to be misuse at dual-class firms and, consequently, place a lower value on cash in these firms in comparison to single-class companies. In the second article we analyze whether audit quality, captured by the well-known Big 4/non-Big 4 dichotomy, impacts the value that investors place on cash holdings in Latin America. Previous literature suggest that a Big 4 auditor are associated with improved financial reporting quality and more credible financial statements that reduces information asymmetry and agency problems. Thus, by hiring a Big 4 auditor a company is signaling to the market that financial statements are of high quality, which limits managers\' ability to expropriate cash holdings at the expense of shareholders. In this sense, we hypothesize in this research that the market discount more the cash of non-Big 4 clients relative to Big 4 clients, everything else equal. Our results, on the other hand, do not support the existence of a Big 4 premium relative to the value that shareholders assigns to a dollar of cash, thereby rejecting the research hypothesis. Moreover, we also find that the market value of cash in Latin America is, on average, almost zero and in some countries even negative. Investors do not expect to receive the full benefits of cash holdings in an environment where their interests are poorly protected. Consequently, anticipating that cash are more likely to be misspent in countries with poor investor protection, then shareholders substantially discount the value of cash in Latin American companies. The aim of the last article is to shed light on the role of accounting conservatism in the determination of cash levels. The literature suggest that conservatism is a governance mechanism that can alleviate part of the agency problems associated with managers\' investment decisions. Thus, we hypothesize that greater conservatism limits managers\' ability for abusing cash for their private benefits. To test this hypothesis, we use the Latin American setting. The analyzes indicate that greater conservatism has the potential to bring real economic benefits to organizations, serving as an efficient mechanism that reduce agency costs over cash management by inducing a more efficient use of cash holdings, all else equal. Therefore, we find results consistent with our predictions, suggesting that firms under more conservative accounting have higher cash levels as a result of the reduction in cash misappropriation.